Agent-based logistic coordination - Syed Mansoor Raza. (2008)
One of the main issues in efficiently integrating a company or industry’s supply chain is the difficulty in coordinating all the activities among all the parties involved, mainly because these parties have different and conflicting objectives. It is insufficient to optimize the operations within a single party involved, while the other parties are not operating at optimal conditions, which result in a poor overall system performance.